ESTIMASI SUMBERDAYA BATUGAMPING DI PT. SEMEN BATURAJA TBK KABUPATEN OGAN KOMERING ULU PROVINSI SUMATERA SELATAN - Azizah, Nurul; Ritonga, Magdalena Ritonga; Marlinda, Lenny (Engineering Faculty Universitas Lampung, 2025)
Limestone is a rock that is generally whitish, fine-grained, composed of calcium carbonate, and formed below sea level. The Sumatra region, especially in the South Sumatra region, has potential mineral resources in the form of limestone located in the Ogan Komering Ulu district. The study area is included in the Baturaja Formation (Nmb) with the Baturaja limestone unit and the Gumai Formation (Nmg) with the Gumai limestone unit, which are stratigraphically deposited in harmony. The formation of origin in the study area is divided into 2, namely the form of structural origin consisting of structural valley landforms (S1), and the form of anthropogenic origin consisting of non-mine landforms (A1), mine slope landforms (A2) and sump landforms (A3). In the research area in the field observations, there is a geological structure in the form of a right horizontal fault. With field observations and the presence of limestone resources in the research area, mining can be carried out in the area. In limestone mining, estimation is needed to be able to calculate resources before the mining process takes place. In this study, the depth of the limestone layer is modelled with a block model with the aim of being able to see the distribution of layers to be estimated. The estimation of limestone resources uses the Inverse Distance Weighting (IDW) method by estimating the value of the area that does not have an inferred value.